Five new species of lapsiine jumping spiders from Ecuador (Araneae: Salticidae) - Maddison, Wayne P. (Zootaxa, 2012)
Five new species of lapsiine jumping spiders from Ecuador are described, including the first Lapsias Simon from outsideVenezuela. Lapsias lorax, sp. nov. is known from a cloud forest just west of Quito. A new species from the slopes of Vol-can Sumaco is tentatively assigned to Lapsias, Lapsias guamani sp. nov. Lapsias canandea, sp. nov. is the first lapsiinedescribed from the lowlands west of the Andes. The genus Lapsias is poorly defined, and some of these new species maymerit separate genera when the group's phylogeny is better known. Two new species of Thrandina Maddison are describedfrom about 2000 m elevation, Thrandina cosanga sp. nov. from the eastern slopes of the Andes, and Thrandina bellavistasp. nov. from the western slopes. New illustrations are provided for the already-described Thrandina parocula Maddison. Photographs of living individuals are presented for all species.